2021
DOI: 10.3390/polym13091457
|View full text |Cite
|
Sign up to set email alerts
|

H2S-Sensing Studies Using Interdigitated Electrode with Spin-Coated Carbon Aerogel-Polyaniline Composites

Abstract: In this paper, carbon aerogel (CA)-polyaniline (PANI) composites were prepared and first applied in the study of H2S gas sensing. Here, 1 and 3 wt% of as-obtained CA powder were blended with PANI to produce composites, which are denoted by PANI-CA-1 and PANI-CA-3, respectively. For the H2S gas-sensing studies, the interdigitated electrode (IDE) was spin-coated by performing PANI and PANI-CA composite dispersion. The H2S gas-sensing properties were studied in terms of the sensor’s sensitivity, selectivity and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 47 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Another example of a sensor reported for the detection of humidity and ammonia was fabricated using carbon nanofibers (CNFs), PANI and PVA [ 12 ]. Other types of gas sensors were recently reported that include an H 2 S sensor based on carbon aerogel (CA) and PANI [ 150 ], and a CO 2 sensor comprising graphene (G)/PANI [ 151 ].…”
Section: Carbon-based Humidity Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of a sensor reported for the detection of humidity and ammonia was fabricated using carbon nanofibers (CNFs), PANI and PVA [ 12 ]. Other types of gas sensors were recently reported that include an H 2 S sensor based on carbon aerogel (CA) and PANI [ 150 ], and a CO 2 sensor comprising graphene (G)/PANI [ 151 ].…”
Section: Carbon-based Humidity Sensorsmentioning
confidence: 99%
“…For example, carbon aerogel materials possess enormous porosity, whereby such types of sensors exhibit an extremely fast response and very slow recovery (cf. Table 6 ) [ 150 ].…”
Section: Carbon-based Humidity Sensorsmentioning
confidence: 99%
“…They explained that aerogel-based composites were first applied on the interdigitated electrode made of glass. Carbon aerogels were dispersed with the spin-coating method on the electrode for gas sensing [ 103 ].…”
Section: Applications Of Aerogelsmentioning
confidence: 99%
“…Nowadays, polyaniline emeraldine salt (PANI) presents encouraging gas sensing properties among the functional materials due to the adjustable conductivity via ion doping, tunable degree of the oxidation/reduction state, and compatible growth on the substrate. Despite the good H 2 S sensing performances reported previously, the low sensitivity of pristine PANI still needs to be enhanced. Hence, the developments of PANI-based nanocomposite materials, including PANI–carbon materials, , PANI–MOSs, , PANI–noble metals, , and PANI–transition metal salts have been intensively investigated for further improvement of the H 2 S sensing properties. Most of them are focused on the formation of the p–n or Schottky junction on the interfaces of PANI rather than the selection of H 2 S-sensitive functional materials; therefore, the restricted sensing performances of PANI-based sensors still need to be enhanced.…”
Section: Introductionmentioning
confidence: 99%